Signal transduction and transforming properties of the TEL–TRKC fusions associated with t(12;15)(p13;q25) in congenital fibrosarcoma and acute myelogenous leukemia - Liu, Qing (Oxford University Press, 2000)
The TEL–TRKC fusion is expressed as a consequence of t(12;15)(p13;q25), and is associated with two human cancers: congenital fibrosarcoma and acute myelogenous leukemia (AML). We report that the T/T(F) and T/T(L) fusion variants associated with congenital fibrosarcoma and AML, respectively, are constitutively tyrosine phosphorylated, and confer factor-independent growth to the murine hematopoietic cell line Ba/F3. Retroviral transduction of T/T(L) causes a rapidly fatal myeloproliferative disease in a murine bone marrow transplant (BMT) model, whereas T/T(F) causes a long-latency, pre-B-cell lymphoblastic lymphoma. TEL–TRKC variants are potent activators of the MAP kinase pathway, but neither variant activates Stat5 or other Stat family members. T/T(L), but not T/T(F), induces tyrosine phosphorylation of phospholipase Cγ (PLCγ), phosphoinositol-3 kinase and SHC. However, mutation analysis demonstrates that PLCγ tyrosine phos phorylation by T/T(L) is dispensable for induction of the myeloproliferative phenotype by T/T(L). Collectively, these data demonstrate that the TEL–TRKC fusion variants are oncoproteins that activate the MAP kinase pathway, and do not require activation of either PLCγ or Stat5 for efficient induction of a myeloproliferative phenotype in the murine BMT model.